FREQUENCY OF DYSLIPIDEMIA IN TYPE 2 DIABETES MELLITUS PATIENTS WITH AND WITHOUT MICROALBUMINURIA (The Research of Medical Science Review, 2025)
Introduction: Dyslipidemia is a common metabolic abnormality in patients with type 2 diabetes mellitus (T2DM), characterized by alterations in lipid profiles, including elevated triglycerides, low high-density lipoprotein cholesterol (HDL-C), and small, dense low-density lipoprotein cholesterol (LDL-C). Objective: To determine the frequency of microalbuminuria in type 2 diabetes mellitus patients. To compare the frequency of dyslipidemia in type 2 diabetic patients with and without microalbuminuria. Methodology: This cross-sectional study was conducted at the Department of General Medicine, KEMU / Affiliated Hospital, Lahore during----. Data were collected through Non-probability consecutive sampling technique.Demographic and clinical data, including name, age, gender, BMI, duration of diabetes, and address, were recorded on a pre-designed proforma. Results: Data were collected from 120 patients, with a mean age of 52.3 ± 11.6 years and a mean BMI of 27.8 ± 4.2 kg/m². The average duration of diabetes was 8.5 ± 4.1 years. Among the participants, 65 (54.2%) were male, and 55 (45.8%) were female. Microalbuminuria was present in 35 (29.2%) patients, while 85 (70.8%) were microalbuminuria-free. Dyslipidemia was observed in 68 (56.7%) patients, with a higher prevalence in those with microalbuminuria. The association between microalbuminuria and dyslipidemia was evident, with 27 (77.1%) of the patients with microalbuminuria showing dyslipidemia compared to 41 (48.8%) without microalbuminuria. Conclusion: It is concluded that dyslipidemia is highly prevalent among patients with type 2 diabetes mellitus, with a significantly higher occurrence in those with microalbuminuria.